Visiting Jackie And Marty Hijmans, Edwards, Colorado - Watkins, Howard::::::::: (1982)
Jackie Hijmans holding Carey Hijmans and Christine Watkins and Adam Watkins on top of ski slope; grass on ground Trees and mountains in background